Do induced twin pregnancies influence the obstetric and neonatal results of multiple births born before 32 weeks? Comparison to spontaneous gestation - Sofia Raposo Dinis; Ana Patrícia Domingues; Adriana Belo; Daniela Couto; Etelvina Fonseca; Paulo Moura (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2015)
PURPOSE: To compare obstetric outcomes of induced preterm twin births (under 32 weeks gestation) with those spontaneously conceived. METHODS: Prospective study of twin pregnancies (25 induced and 157 spontaneously conceived) developed over a period of 16 years in a tertiary obstetric center. Demographic factors, obstetric complications, gestational age at delivery, mode of delivery, birth weight and immediate newborn outcome were compared. RESULTS: The analysis of obstetrical complications concerning urinary or other infections, hypertensive disorders of pregnancy, gestational diabetes, fetal malformations, intrauterine fetal death, intrauterine growth restriction and intrauterine discordant growth reveal no significant statistical differences between the two groups. First trimester bleeding was higher in the induced group (24 versus 8.3%, p=0.029). The cesarean delivery rate was 52.2% in spontaneous gestations and 64% in induced gestations. Gestational age at delivery, birth weight, Apgar scores at first and fifth minutes, admissions to Neonatal Intensive Care Unit and puerperal complications show no statistically significant differences between the two groups. These results were independent of chorionicity and induction method. CONCLUSION: The mode of conception did not influence obstetric and neonatal outcomes. Although induced pregnancies have higher risk of first trimester bleeding, significant differences were not observed regarding other obstetric and puerperal complications and neonatal results.